Is Self-Employment for Migrants? Evidence from Italy - Marianna Brunetti; Anzelika Zaiceva (Global Labor Organization (GLO), 2023)
Using a unique Italian dataset covering the period 2004-2020, we assess the immigrant-native gap in entrepreneurship and investigate channels behind it. The data allows us to account for many observable characteristics as well as for risk aversion, which is usually not observed, yet crucial for the self-employment decision. Unlike most of the existing empirical literature, we find that immigrants in Italy are less likely to be self-employed. The negative gap is confirmed when propensity score matching methodology is used. Heterogeneity analysis suggests that the negative gap is larger for men, for economic migrants and those coming from Sub-Saharan Africa, while it is not significant for mixed immigrant-native couples, for highly skilled, and for migrants from Asia and Oceania. The largest gap is found for those working in the agricultural sector. Regarding additional channels, we explore the role of access to credit, including the informal one, and whether migrants are credit constrained, as well as the importance of migrant networks, easiness of doing business, and expenditures on services for migrants. Despite finding significant correlations between self-employment and some of these factors, none of them seem to decrease the magnitude of the negative gap.
Keywords: F22; J21; O15; J15; 330; immigrants; self-employment; gender; intermarriage; propensity score matching